As jornadas de junho de 2013 e as estratégias de ação da Mídia Ninja no campo do jornalismo - Mendonça, Marcela Prado (2016)
This research aims to understand how Mídia N.I.N.J.A. (Independent Narratives, Journalism and Action in Portuguese) emerged from political actor within the political field, to a media actor within the media field, and its movement within the journalism field during the Journeys of June 2013 in order to conquer the symbolic capital of visibility. The phenomenon known as "Journeys of June" provides the space of time for this research. In June 2013, the Mídia Ninja (MN) conquered space on the pages of mainstream newspapers in both Brazilian and international presses. In order to understand the object Mídia Ninja, we follow the conceptual construction of Pierre Bourdieu's field, in order to relate the different spheres of activity of this collective actor, analyzing the struggles for symbolic capital and its relationship with the traditional press in the field of journalism. We investigated the Ninja Media as a social movement that acts in social media, based on the authors Maria Gloria Gohn and Ilse Scherer-Warren, in order to understand the collective configuration as a new social movement and analyze its appropriation of new information technologies (ICT's) to the media cyberactivism and the concept of collective action repertoire of Charles Tilly. From the identification of the group's action repertoire, the MN was located in the field of journalism and had their actions related with the actions of traditional media, using the newspapers Folha de S. Paulo and O Estado de S. Paulo. This analysis allowed us to investigate the following hypotheses: 1) Mídia Ninja is a new social movement that has appropriated new information and communication technologies to achieve media visibility; (2) that Mídia Ninja's actions express a kind of symbolic fight for the symbolic capital of the media field that is visible, to the consequent conquest of power within the political field; (3) the actions of Mídia Ninja has generated a collective position within the field recognized by the own journalism agents' field , representatives of the traditional press and finally (4) the Mídia Ninja overthrew the journalism field during Journeys of June.